Floristic and Forest Inventory of Santa Catarina: species of evergreen rainforest - Gasper,André Luís de (2014)
This study presents the list of species of Evergreen Rainforest in Santa Catarina, based on 202 sample units established by the Floristic and Forest Inventory of Santa Catarina, in order to study the tree/shrub component and regeneration in addition to a floristic survey outside the sample units. We recorded 1,473 species: three gymnosperms and 1,470 angiosperms, that totalize 19% of all species quoted for this Brazilian forest type. The most species-rich families were Orchidaceae (143 species), Myrtaceae (142), Asteraceae (98), Melastomataceae (86), Fabaceae (78), Rubiaceae (65), Solanaceae (61), Bromeliaceae (57), Piperaceae (56), and Lauraceae (52). Among them are eight species listed in the Official List of Endangered Species of the Brazilian Flora: Aechmea blumenavii, Araucaria angustifolia, Billbergia alfonsijoannis, Euterpe edulis, Heliconia farinosa, Ocotea catharinensis, O. odorifera and, O. porosa.